Alinhamento estratégico entre os planos de tecnologia da informação e os planos de negócio: uma análise dos fatores influenciadores - Freitas, Paulo Luis Carvalho de (2007)
In recent years the subject, strategical alignment, has been treated for several authors of the area as an important tool of enterprising management, which provides to the company, conditions to act in way integrated with its business-oriented areas, optimizing resources in order to reach efficiently its objectives. This study it was done in two great companies, with the proposal to know how they make possible the strategical alignment among the Information Technology and Business Plans to guide the internal and external actions of each company being aimed the market demands where they act. This reseach used the multicase and collected data methods through an instrument adapted for this study and semi-structuralized interviews, on the basis of the models of Strategical Alignment by Henderson and Venkatraman (1993), Maturity of Alignment by Luftman (2000) and described the Critical Factors of Success by Teo and Ang (1998) as strategical alignment facilitators. Since the analysis from the answers, the orientation of the strategical alignment of each company can be identified, as well as the level of maturity of it among the IT area and other areas of business from the same ones and, the critical factors of success that also must deserve special attention of the management, to enhance the possibilities of a successful relationship among the Strategical Information Technology Plans and Strategical business Plans. The results of the research presented elements that will serve of base for future studies, pointing out the importance of the balance that must exist among the areas of business with the area of IT to any company, to optimize the performance and reach the desired effectiveness